Combined with co-hydrothermal carbonation of wood waste and food waste digestate for enhanced gasification of wood waste. (1st January 2023) - Zhu, Xiefei; Guo, Wenwen; Luo, Zejun; Zhu, Xinzhe; Cai, Wenfei; Zhu, Xifeng
Graphical abstract: Highlights: Hydrochar was fabricated from FWD and WW by hydrothermal carbonization. The addition of FWD enhanced the gasification activity of hydrochar. Gasification activity dropped gradually with the decrease of metal composition. Volumetric and grain models were used to reveal the gasification mechanism. Activation energy of hydrochar gasification was in the range of 121.03–201.37 kJ mol −1 . Abstract: Energy recovery from carbonaceous solid waste has great potential for waste management and clean sustainable energy production. In this study, incorporating co-hydrothermal carbonization of food waste digestate to improve the gasification of wood waste hydrochar was novelly proposed. Based on the metal compositions and surface properties, the gasification characteristics of the hydrochar were investigated at different temperatures using a thermogravimetric analyzer (TGA). The results indicated that the hydrochar prepared by co-hydrothermal carbonization had abundant surface functional groups and metal components such as calcium (up to 124.25 mg g −1 ). The addition of food waste digestate significantly improved the gasification activity (up to 7.2 folds at 900 °C) of the hydrochar and reduced the gasification reaction time. Furthermore, the gasification activity of hydrochar was positively correlated with the metal composition content. Both volumetric and grain models showed good fitting effects, and the apparent activation energy of hydrochar gasification for both models was in the range of 121.03–201.37 kJ mol −1 . This novel pathway advocated here for the efficient co-conversion of solid waste provides a new perspective for the large-scale utilization of solid waste.